The First Dental Visit - Ghimire, Neeta; Kayastha, B; Nepal, P (Journal of Chitwan Medical College, 2014)
Oral health is a vital part of overall infant health. An early dental visit is important in rendering prevention oriented intervention and parental counselling regarding the oral health. To assess the age and common chief complaint of the children in their first dental visit. This was a retrospective study done using case records of 842 children, who reported to the Department of Pedodontics and Preventive Dentistry, chitwan medical college. The age groups were divided into four categories; less than 3 years, 3-6years, 7-11 years and 12-14 years. The various chief complaints of patient were categorized as follows; routine check up, dental caries, dental pain, deposits/bad breath, malocclusion, unerupted ,missing or extra tooth, oral habits, trauma, orientation to prevention and others (cleft lip, palate, natal/neonatal teeth, mobile teeth, soft tissue lesions and others). The age group and the most common complaint at the first dental visit were assessed. Majority of children who visited the dentist were of age 7-11 years with the most common reason for their visit being pain followed by dental caries. None of the children visited for regular check up within 6 months of eruption of first tooth, though few children of that age group visited the dentist for other reasons like cleft lip/palate, natal/ neonatal tooth etc. The reason behind the first dental visit is when there is a problem. The most common age group to visit dentist was 7-11years with the commonest reason for their visit being pain and dental caries. It can be concluded that awareness and knowledge regarding the first dental visit is almost nil among the parents of this region. Journal of Chitwan Medical College 2013; 3(4); 30-33 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9551